Exploring Changing Practices and Influence of Artificial Inteligence on Modern Journalism - Chetouani, Nour (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Journalism in the rapidly evolving modern world is undergoing significant transformation due to the rise of artificial intelligence applications. The study explores the impact of artificial intelligence (AI) on modern journalism, including its transformative effects on news production, distribution, and consumption. This study explores the intricate relationship between AI applications and evolving journalism practices. Through an analysis of industry trends and case studies, we have identified the multidimensional impact of the applications on newsrooms, information collections, and reporting. We have highlighted both the opportunities and challenges brought about by this technologıcal paradigm shift in the field. The study aims to offer a detailed comprehension of the developing relationship between artificial intelligence (AI) applications and contemporary journalism. The results provide significant insights for scholars, practitioners, and stakeholders concerning the dynamic intersection of technology and media.